Towards a continental Open Science Vision: Decolonising Open Science Symposium: Scholarly Communication - Mchunu, Nokuthula P. (My University, 2024)
The presentation was held at the symposium hosted by FORM bringing together leading representatives from PKP, DOAJ, Al Qasimi Foundation, The National Research Foundation of South Africa (NRF), and NYU Abu Dhabi to discuss the theoretical and practical implications of global biases in academia. More information on the Symposium can be found at https://forumforopen.org/events/decolonising-open-science-symposium-dismantling-global-hierarchies-of-knowledge/